Towards the design of contrast-enhanced agents: systematic Ga3+ doping on magnetite nanoparticles. Issue 6 (21st January 2022) - Galarreta-Rodriguez, Itziar; Marcano, Lourdes; Castellanos-Rubio, Idoia; Gil de Muro, Izaskun; García, Isabel; Olivi, Luca; Fernández-Gubieda, M. L.; Castellanos-Rubio, Ainara; Lezama, Luis; de Larramendi, Idoia Ruiz; Insausti, Maite
Abstract : The main objective of the preparation of the Fe3− x Ga x O4 (0.14 ≤ x ≤ 1.35) system was to further the knowledge of the magnetic response of Ga 3+ -doped magnetite for application as MRI contrast agents. Abstract : The main objective of the preparation of the Fe3− x Ga x O4 (0.14 ≤ x ≤ 1.35) system was to further the knowledge of the magnetic response of Ga 3+ -doped magnetite for application as MRI contrast agents. With this purpose, monodisperse nanoparticles between 7 and 10 nm with different amounts of gallium were prepared from an optimized protocol based on thermal decomposition of metallo-organic precursors. Thorough characterization of the sample was conducted in order to understand the influence of gallium doping on the structural, morphological and magnetic properties of the Fe3− x Ga x O4 system. X-ray diffraction and X-ray absorption near-edge structure measurements have proved the progressive incorporation of Ga in the spinel structure, with different occupations in both tetrahedral and octahedral sites. Magnetization measurements as a function of field temperature have shown a clear dependence of magnetic saturation on the gallium content, reaching an M s value of 110 Am 2 kg −1 at 5 K for x = 0.14 (significantly higher than bulk magnetite) and considerably decreasing for amounts above x = 0.57 of gallium. For this reason, nanoparticles with moderate Ga quantities were water-transferred by coating them with the amphiphilic polymer PMAO to further analyse their biomedical potential. Cytotoxicity assays have demonstrated that Fe3− x Ga x O4 @PMAO formulations with x ≤ 0.57, which are the ones with better magnetic response, are not toxic for cells. Finally, the effect of gallium doping on relaxivities has been analysed by measuring longitudinal (T1 −1 ) and transverse (T1 −1 ) proton relaxation rates at 1.4 T revealing that nanoparticles with x = 0.14 Ga 3+ content present remarkable T2 contrast and the nanoparticles with x = 0.26 have great potential to act as dual T1 –T2 contrast agents.